Impaired Localization of Claudin-11 in Endometriotic Epithelial Cells Compared to Endometrial Cells. (September 2019) - Horné, Fabian; Dietze, Raimund; Berkes, Eniko; Oehmke, Frank; Tinneberg, Hans-Rudolf; Meinhold-Heerlein, Ivo; Konrad, Lutz
Claudins are the major components of tight junctions and are often deregulated in human cancer, permitting escape of cancer cells along with the acquisition of invasive properties. Similarly, endometrial cells also show invasive capabilities; however, the role of tight junctions in endometriosis has only rarely been examined. In this study, we analyzed the protein expression and localization of claudin-7 and claudin-11 in human eutopic and ectopic endometrium and endometrial cell lines. We identified claudin-7 primarily at the basolateral junctions of the glandular epithelial cells in eutopic endometrium as well as in the ectopic lesions in nearly all glands and cysts. Quantification of claudin-7 localization by HSCORE showed a slight increase in peritoneal and deep infiltrating endometriosis (DIE) compared to eutopic endometrium. In contrast, claudin-11 was localized mainly in the apicolateral junctions in nearly all glandular epithelial cells of the eutopic endometrium. Interestingly, we observed a deregulation of claudin-11 localization to a basal or basolateral localization in ovarian ( P < .001), peritoneal ( P < .01), and DIE ( P < .05) and a moderately decreased abundance in ovarian endometriosis. In endometrial cell lines, claudin-7 was only present in epithelial Ishikawa cells, and silencing by small-interfering RNA increased cell invasiveness. In contrast, claudin-11 could be demonstrated in Ishikawa and endometriotic 12Z and 49Z cells. Silencing of claudin-11 decreased invasiveness of 12Z slightly but significantly in 49Z. We suggest that although claudin-7 and claudin-11 can be found in nearly all eutopic and ectopic epithelial cells, the impaired localization of claudin-11 in ectopic endometrium might contribute to the pathogenesis of endometriosis.